DRIVING FASHION MSMES SUCCESS: A LOOK AT WOMEN ENTREPRENEURS MINDSET, MOTIVATION, AND STRATEGY - Fasmita, Windy; Ie, Mei (International Journal of Application on Economics and Business, 2025)
This study examines the influence of entrepreneurial mindset and entrepreneurial motivation on the success of women’s fashion MSMEs in Central Jakarta, with business strategy serving as a moderating variable. Employing a descriptive quantitative approach with purposive sampling, the study involves 306 respondent who are owners of women’s fashion MSMEs. Data analysis was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM) to evaluate the relationships between variables. The findings indicate that an entrepreneurial mindset has a positive and significant impact on the success of women’s fashion MSMEs in Central Jakarta. Similarly entrepreneurial motivation positively and significantly influences business success. Business strategy also demonstrates a positive and significant effect on success while moderating the relationship between entrepreneurial mindset and business success. However, business strategy as a moderator in the relationship between entrepreneurial motivation and business success shows a negative but significant influence, highlighting the need to align strategies with individual entrepreneurial motivation. These results suggest that MSMEs entrepreneurs can enhance business success by cultivating an innovation driven mindset, growth orientation, and risk-taking ability. Strong entrepreneurial motivation drives concrete actions toward business development, enabling entrepreneurs to remain focused despite challenges. The implications of this study emphasize the importance of improving entrepreneurial skills, aligning strategies with motivations, and fostering resilience to achieve sustained success. Women’s fashion MSME entrepreneurs are encouraged to maximize their business potential and succeed in a competitive market environment.